Media literacy : thinking critically about video games & virtual worlds - Paxson, Peyton. 4 0 16; 5 (Portland, ME : Walch Education, 2009)
A comprehensive guide to media literacy that focuses on video games and virtual worlds, providing five teaching units, with activities and reproducible pages, for students to examine the positive and negative aspects of video games, their effect on society, why people play, the industry, and other related topics.
Includes bibliographical references (p. 153-154).
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching (Middle school);Social aspects;Study and teaching (Middle school);Social aspects;Study and teaching (Middle school);Social aspects;Study and teaching (Middle school);Study and teaching (Secondary);Social aspects;Study and teaching (Secondary);Social aspects;Study and teaching (Secondary);Social aspects;Study and teaching (Secondary);Study and teaching.;Social aspects;Study and teaching.;Social aspects;Study and teaching.;Social aspects;Study and teaching. -- Media literacy;Video games;Computer games;Mass media;Media literacy;Video games;Computer games;Mass media;Media literacy;Video games;Computer games;Mass media -- Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs; 20; 2